Ecologia e comportamento da formiga Camponotus sericeiventris Guérin, 1838 (Formicinae, Camponotini) no cerrado - Yamamoto, Marcela (2004)
The carpenter ant, Camponotus sericeiventris, received this denomination due its habit of to nest inside the wood. This species is spread in the Neotropical region, being present in a large amount of ant communities and interactions studies. The present study provides further qualitative and quantitative data about the natural history and feeding behavior of C. sericeiventris, including dietary requirements and spatial foraging pattems. Additionally the study describes the behavioral repertoire, hanging polymorphism and division of labor and the evidence of age polyethism. The nests occur inside dead or live trunks, and also in branches with soft wood. Ant activity is positively correlated with temperature and negatively with humidity. Foragers scarch for food individually or in groups, on the ground or climbing onto the foliage, within a ray of 14 m around the nest. There is overlap in the foraging area among neighbor colonies (as far as 28 m). The workers are opportunistic feeders that visiting flowers and extrafloral nectaries, attending Ilemiptera and Lepidoptera, collecting seeds and fruits, and hunting for live prey as well as scavenging for dead animais. The behavioral repertoire of C. sericeiventris is complex with 67 behavioral acts divided in eight categories. The behavioral analysis showed evidence of age polyethism and revealed labor division among the three physical sizes of the workers. This behavior indicates high levei of social organization in C. sericeiventris, and the interactions with plants and other animais suggest that species has a complex ecology function in the environment.